(untitled) (Research, Society and Development, 2022)
The present study aimed to compare the incentive, training conditions and motivational aspects of female and male futsal practitioners in the Vale do Ivaí region of the state of Paraná. The research was characterized as a qualitative and quantitative study and was composed of a sample of 16 athletes belonging to the under-15 and under-17 categories of 8 teams (4 female teams and 4 male teams) from the region of Vale do Ivaí, in addition to 6 coaches of the respective teams. The teams from the cities of Arapuã, Ivaiporã, Manoel Ribas and Jardim Alegre took part in the research. As instruments, a structured interview prepared by the researchers was used to investigate the training conditions and to assess the levels of motivation, the Sports Motivation Scale (SMS-2) was used. Data were collected individually with each participant (interviews and completion of the questionnaire. For data analysis, the distribution of relative and absolute frequencies was used to categorize the answers of the interviews, and, for quantitative data, the Shapiro-Shapiro test was used. Wilk and t test for independent samples, p<0.05 was adopted as a significance level. The results showed that even with lower structural conditions, female futsal athletes showed a higher level of intrinsic regulation motivation (p=0.038*) , regarding the comparisons of incentives and training conditions, it was observed that male athletes participate in a greater number of competitions, however, the resources and structures used for training and competitions are similar between genders. women participate in a smaller number of competitions and use similar structures, they are more motivated than male athletes. males for the investigated sample.